Clinical clues predictive of Stevens-Johnson syndrome as the cause of chronic cicatrising conjunctivitis. Issue 7 (19th October 2019) - Shanbhag, Swapna S; Chanda, Sanjay; Donthineni, Pragnya Rao; Sane, Sayali Sanjeev; Priyadarshini, Smruti Rekha; Basu, Sayan
Abstract : Purpose: This study aimed to identify the clinical clues in patients with chronic cicatrising conjunctivitis (CCC), that were suggestive of Stevens-Johnson syndrome (SJS) as the aetiology. Methods: This was a cross-sectional observational study of 75 patients presenting with CCC from 2016 to 2018. Those with a documented diagnosis of SJS (n=43) were included as cases; while those with a positive serology or tissue biopsy for a non-SJS condition were included as controls (n=32). The features in the medical history and clinical examination that were positively and negatively associated with SJS were scored +1 and −1, respectively. A receiver operating characteristic (ROC) curve analysis was performed to detect the threshold score for optimal sensitivity and specificity of the scoring system. Results: No single feature had absolute sensitivity and specify for SJS. The 10 positive features suggestive of SJS (p<0.0001) included (1) history of: acute conjunctivitis, fever or drug intake preceding conjunctivitis, peeling of skin on pressure, loss of nails and severe morbidity with hospital admission; and (2) clinical features of: skin discoloration, nail disfigurement, lip-margin dermalisation, lid-margin keratinisation and distichiasis. The two negative criteria were history of mucosal ulcers without skin involvement and recurrent mucosal ulceration. On ROC analysis, a score of >5 showed a sensitivity of 90.7% and specificity of 93.8% for the diagnosis of SJS. Conclusions: The combination of clinical clues identified in this study can help clinicians confirm SJS as the aetiology of conjunctival cicatrisation, especially when reliable documentation of the acute episode is not available.